2019
DOI: 10.1097/sle.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic, Radiological, and Quality of Life Outcome of Paraesophageal Hernia Repair With Urinary Bladder Extracellular Surgical Matrix: Comparison With Primary Repair

Abstract: Introduction: Paraesophageal hernia repairs are prone to recurrence and mesh reinforcement is common. Both biologic and prosthetic meshes have been used. We report a comparison of a new type of biologically derived graft, Gentrix Surgical Urinary Bladder Matrix (UBM). Methods:The medical records of 65 patients who underwent paraesophageal hernia repair (PEHR) were reviewed. Primary data points included demographics, first-time or recurrent hernia, operative approach, graft or primary repair, operative time, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…reported a significant difference in QoL between mesh and no-mesh groups ( P <0.0001),[ 19 ] however the remaining five studies found no statistically significant difference in the two groups. [ 16 20 41 61 62 ] Two studies used mesh in all the patients;[ 31 39 ] At 2 years follow up with barium examination and endoscopy, Hazebroek et al . [ 31 ] found no mesh erosion and only one asymptomatic recurrent hernia of <2 cms.…”
Section: Resultsmentioning
confidence: 99%
“…reported a significant difference in QoL between mesh and no-mesh groups ( P <0.0001),[ 19 ] however the remaining five studies found no statistically significant difference in the two groups. [ 16 20 41 61 62 ] Two studies used mesh in all the patients;[ 31 39 ] At 2 years follow up with barium examination and endoscopy, Hazebroek et al . [ 31 ] found no mesh erosion and only one asymptomatic recurrent hernia of <2 cms.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the presence of ulcers and the location of the ulcers in patients is not known. Furthermore, it has been shown that as the ulcer regresses with hiatal hernia repair, anemia can also be treated, and complications that may be caused by hiatal hernia can be prevented (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…UBM reinforcement facilitated the repair of a large hiatal hernia concomitant with a sleeve gastrectomy surgery ( Figure 4 M–O) [ 128 ]. UBM-reinforced repair of paraesophageal hernia was associated with fewer recurrences of severe symptoms as compared with primary repair [ 129 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%